Does homesickness undermine the potential of job resources? A perspective from the work–home resources model. (27th June 2017) - Du, Danyang; Derks, Daantje; Bakker, Arnold B.; Lu, Chang‐qin
Summary: Rapid economic development in recent decades has resulted in a considerable increase in the number of people working far away from their home locations. Homesickness is a common reaction to the separation from home. Our research uses the work–home resources model to explain how the experience of homesickness can undermine the positive effect of job resources on job performance (i.e., task performance and safety behavior). In addition, we hypothesize that emotional stability and openness are key resources that can buffer the negative interference of homesickness with the job resources–performance relationship. We conducted two studies to test our hypotheses. Study 1 was a two‐wave longitudinal study using a migrant manufacturing worker sample. In this study, homesickness was measured at the between‐person level, and performance was measured three months later. Study 2 was a daily diary study conducted in a military trainee sample. In this study, homesickness was measured at the within‐person level to capture its fluctuations over 20 days, and daily job performance was assessed using supervisor ratings. Both studies showed evidence of the hypothesized moderating effect of homesickness and three‐way interaction effects of job resources, homesickness, and key resources (i.e., emotional stability and openness) on task performance and safety behavior.